Minimizing surface reflectance of crystalline silicon: A simulation based study. Issue 1 (July 2021) - Das, Tiasa; Kumar, Sandip; Upadhyay, Anamika; Goswami, Arjyajyoti
Abstract: Silicon has been a popular choice for optoelectronic devices and solar cells since its discovery mainly due to its abundance in nature. However, methods to improve light trapping and hence increase the efficiency of these devices has always been a subject of great interest. The objective of this study has been to minimize the surface reflectance of thin film silicon through use of anti-reflection coating and surface patterning. In this study, the most effective anti-reflectance coating (ARC) is determined amongst three well known materials namely, Silicon Nitride(Si3 N4 ), Titanium Dioxide(TiO2 ) and Magnesium Fluoride (MgF2 ) by simulation through S4 software by implementing Rigorous Coupled Wave Analysis Algorithm (RCWA). The best possible combination of the substrate and ARC is determined for a working wavelength range of 300 nm to 900 nm by varying the thickness of ARC. The best possible combination of substrate and ARC has been subjected to further investigation by imparting patterns and minimum average reflectance of 0.135986 was obtained experimentally.